Philosophy of Religion A-Z - Quinn, Patrick (Philosophy A-Z : PAZ, 2022)
GBS_insertPreviewButtonPopup('ISBN:9780748620548);A concise alphabetical guide to the philosophical investigation of religion and the meaning of religious beliefs.Philosophy of Religion A-Z provides an overview of the main themes, key figures and issues in the subject. Both topical and historical, it examines key concepts from the Absolute and the Afterlife to World Religions and Yoga as well as thinkers from Abraham to Wittgenstein. The relationship between philosophy and theology is examined as is that between religion, faith and belief. Extensive cross-references demonstrate clear connections between entries.This reference guide will be useful for anyone interested in the philosophy of religion, in philosophy and theology as well as in anthropology, cultural and religious studies, mythology and the psychology and sociology of religion.Key FeaturesThe alphabetical presentation of the issues and thinkers involved makes for ease of reading.Philosophers' views on religion are objectively and sympathetically presented as are the various religious creeds discussed.